2017
DOI: 10.1590/1809-2950/17495424022017
|View full text |Cite
|
Sign up to set email alerts
|

Perfil dos docentes e do conteúdo de disciplinas de Fisioterapia em Saúde da Mulher ministradas em Instituições de Ensino Superior (IES) públicas no Brasil

Abstract: RESUMO Foi realizado um estudo transversal descritivo em que se avaliou o perfil dos docentes e o conteúdo ministrado em disciplinas de Fisioterapia em Saúde da Mulher em Instituições de Ensino Superior (IES) públicas do Brasil. Docentes da área de Fisioterapia em Saúde da Mulher ou áreas afins de instituições públicas brasileiras foram convidados a preencher um questionário estruturado, contendo questões sobre dados pessoais, formação acadêmica, atuação profissional e conteúdo programático da disciplina. Os d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
1
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 7 publications
1
1
0
2
Order By: Relevance
“…In terms of their own work process, 63.20% of the professors reported that they were unable to maintain the desired level of quality(Table 2).Participants in the present study were professors from graduate physical therapy courses at public and private higher education institutions distributed across the different regions of Brazil. Although the vast majority of these courses are offered at private HEIs, there was a balance between professors from both types of institutions in the study sample.Studies that characterize professors in Brazilian graduate physiotherapy programs are scarce, and as such, our aim was to understand the profile of the professionals currently working at HEIs in the country.Most of the participants were women, with similar findings reported by other authors [16][17][18]. Because this…”
supporting
confidence: 89%
“…In terms of their own work process, 63.20% of the professors reported that they were unable to maintain the desired level of quality(Table 2).Participants in the present study were professors from graduate physical therapy courses at public and private higher education institutions distributed across the different regions of Brazil. Although the vast majority of these courses are offered at private HEIs, there was a balance between professors from both types of institutions in the study sample.Studies that characterize professors in Brazilian graduate physiotherapy programs are scarce, and as such, our aim was to understand the profile of the professionals currently working at HEIs in the country.Most of the participants were women, with similar findings reported by other authors [16][17][18]. Because this…”
supporting
confidence: 89%
“…A prevalência dos profissionais de fisioterapia quanto ao gênero também pode variar a depender do tipo de especialização ou área de atuação. Driusso et al 12 realizaram uma pesquisa com 51 docentes da disciplina de fisioterapia em saúde da mulher em 39 universidades públicas e os resultados mostraram que 96,1% do corpo docente é composto por mulheres jovens e apenas 3,9% por homens. Sousa e Santana 13 trazem que a escolha da especialização do fisioterapeuta em saúde da mulher permeia um grande tabu e que isso acontece devido à baixa procura e ao preconceito estabelecido pela sociedade ao associar-se a ginecologia com profissionais do sexo masculino; e que essa especialidade exige do profissional uma mistura de atributos amadurecidos, que quando preciso, permita aos pacientes confiança aos detalhes íntimos e pessoais de sua vida.…”
Section: Resultsunclassified
“…The participation of this professional reflects the concern with comprehensive care and the search for the return of women as protagonists in childbirth with the decentralization of the physician's role and less obstetric interventions. In the same direction, the prevalence of nurses and physiotherapists in the national scenario is the result of the search for a comprehensive health model, based on the guidelines of these professions (51)(52) . Nurses are the professionals who accompany women throughout the puerperal-pregnancy period and the first contact with women's health care (53) .…”
Section: Discussionmentioning
confidence: 99%